FACTORS ASSOCIATED WITH DOWN SYNDROME INCIDENCE IN BATAM CITY STATE SPECIAL SCHOOL. - Mariaman Tjendera; Siti Iqbalwanty (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : Down Syndrome is a type of mental retardation caused by genetic material on chromosome 21. This syndrome can occur due to a process called nondisjunction or failure to separate. The purpose of this study was to determine the description of the factors associated with the incidence of Down Syndrome in Batam City State Special School. Method :The research design was carried out descriptively. The sampling technique was total sampling, with a sample size of 200 students. The univariate analysis is presented in the frequency distribution table. Result :The results showed that the factors associated with the incidence of Down syndrome were 184 children (92.0%) who did not have Down syndrome, 20 people (10.0%), the mother's age> 35 years. conclusion : The conclusion is that the majority is in the factor of maternal age. The suggestion of this research is that it can be used as input for more intensive counseling to the public about the factors that will cause Down syndrome by paying attention to the lifestyle of good mothers and fathers. So that it can be detected early and can reduce chromosomal abnormalities in the incidence of Down syndrome.